GDF-15 Is Associated with Cancer Incidence in Patients with Type 2 Diabetes. (6th January 2020) - Pavo, Noemi; Wurm, Raphael; Neuhold, Stephanie; Adlbrecht, Christopher; Vila, Greisa; Strunk, Guido; Clodi, Martin; Resl, Michael; Brath, Helmut; Prager, Rudolf; Luger, Anton; Pacher, Richard; et al.
Abstract: BACKGROUND: Diabetes has been linked epidemiologically to increased cancer incidence and mortality. Growth differentiation factor 15 (GDF-15) is increased in patients with diabetes and has recently been linked to the occurrence of cancer. We investigated whether circulating GDF-15 concentrations can predict the incidence of malignant diseases in a diabetic patient cohort already facing increased risk for cancer. METHODS: We prospectively enrolled a total of 919 patients with type 2 diabetes and no history of malignant disease, who were clinically followed up for 60 months. GDF-15, N-terminal pro-B-type natriuretic peptide and troponin T were measured at baseline; an additional 4 cardiovascular biomarkers were determined for a subpopulation (n = 259). Study end point was defined as the first diagnosis of any type of cancer during the follow-up period. RESULTS: During a median follow-up of 60 months, 66 patients (7.2%) were diagnosed with cancer. Baseline circulating GDF-15 concentrations were higher in patients that developed cancer over the follow-up period when compared to cancer-free patients. Increased GDF-15 concentrations were significantly associated with cancer incidence [crude hazard ratio (HR) per 1-IQR (interquartile range) increase 2.13, 95% CI 1.53–2.97, P < 0.001]. This effect persisted after multivariate adjustment with an adjusted HR of 1.86 (95% CI 1.22–2.84; P = 0.004). Among the 4 additionally tested cardiovascular markers in the subpopulation, only troponin T and C-terminal proendothelin-1 showed a significant association with future cancer incidence with unadjusted HRs of 1.71 (95% CI 1.28–2.28, P < 0.001) and 1.68 (95% CI 1.02–2.76, P = 0.042), respectively. CONCLUSIONS: Increased circulating concentrations of GDF-15 are associated with increased cancer incidence in patients with type 2 diabetes.